2007
DOI: 10.1109/tuffc.2007.309
|View full text |Cite
|
Sign up to set email alerts
|

Direct comparison of feature tracking and autocorrelation for velocity estimation

Abstract: Abstract-Feature tracking is an algorithm for estimating tissue motion and blood flow using pulse-echo ultrasound. It was proposed as a computationally simpler alternative to other techniques such as autocorrelation and time-domain cross correlation. The advantage of feature tracking is that it selectively extracts easily identifiable parts of the speckle signal (e.g., the local maxima), reducing the amount of information being processed. Studies on feature tracking to date have used stationary, specklegenerat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Significant gray scale features found by t -test with textural differences were extracted and was given to SVM along with the degree of stenosis feature. 116 Feature analysis is performed for a period of time by plaque risk index and can indicate how the feature vector varies as the case changes from asymptomatic to symptomatic. Local binary pattern (LBP) is a grayscale-invariant texture feature calculated from texture of the local neighborhood.…”
Section: Feature Extraction and Classificationmentioning
confidence: 99%
“…Significant gray scale features found by t -test with textural differences were extracted and was given to SVM along with the degree of stenosis feature. 116 Feature analysis is performed for a period of time by plaque risk index and can indicate how the feature vector varies as the case changes from asymptomatic to symptomatic. Local binary pattern (LBP) is a grayscale-invariant texture feature calculated from texture of the local neighborhood.…”
Section: Feature Extraction and Classificationmentioning
confidence: 99%
“…The experimental setup was similar to the one used in our previous studies [21] and is briefly described here. a commercial flow phantom (optimizer rmI 1425, Gammex, middleton, WI) was used to simulate blood flow.…”
Section: Methodsmentioning
confidence: 99%
“…The results suggested that feature tracking exhibits a comparable estimation mean to the conventional commercial method and a favorable estimation variance [21].…”
mentioning
confidence: 91%
“…Angle-independent CFI, on the other hand, depends on measurement of axial displacements along the axis of two or more ultrasound beams and does not suffer from this problem to the same extent. Langeland et al [38] have compared time domain displacement estimators for 2D tracking, Løvstakken et al [39] have described a more qualitative method which provides an intuitive and detailed display of flow direction, and Bashford and Robinson [40] have compared feature tracking (a variant of speckle tracking) with complex autocorrelation for velocity estimation.…”
Section: Speckle Trackingmentioning
confidence: 99%